Identification of hydrochemical processes and assessment of groundwater quality: a case study of the intergranular aquifer in Dili City, Timor-Leste - Marçal Ximenes; João A. M. S. Pratas; José M. M. De Azevedo; Fernando. P. O. O. Figueiredo; Mattew Currell (Geology, Ecology, and Landscapes)
Drinking water quality is a major concern in Quaternary sedimentary areas with unplanned urban growth and poor waste management, like Dili City, which relies heavily on groundwater to meet daily needs. This study assesses the suitability of groundwater for drinking by analyzing 113 samples from domestic wells, taking into account natural and human influences. The analysis focuses on major and minor ions (Ca²⁺, Mg²⁺, Na⁺, K⁺, SO₄²⁻, HCO₃⁻, F⁻), physicochemical parameters (pH, electrical conductivity, total dissolved solids), and toxic elements (Mn, Fe, Pb, Al, As, Zn, Cd, Ni). Statistical methods (PCA and HCA) are used to determine the group of water types and trace chemical origins, while the Water Quality Index (WQI) assesses drinking suitability. Groundwater types identified include Ca-Cl-HCO₃, mixed Ca-Mg-HCO₃, Na-HCO₃, mixed Na-Cl-HCO₃, and Ca-HCO₃, with Ca-Mg-HCO₃ being the most common. The major ions are ordered as Ca > Na > Mg > K and HCO₃ > SO₄ > Cl. The Gibbs diagram shows the main geochemical processes are rock-water interactions, especially silicate and carbonate weathering. Organic matter and human activities also play a role. The WQI shows that 93.81% of the samples are “excellent” for drinking, while 2.65% and <1% are “good” and “poor” quality respectively.